2015
DOI: 10.1007/s12199-015-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cigarette smoking and one leg with eyes closed balance in Japanese men

Abstract: Objective To investigate the link between cigarette smoking and one leg with eyes closed balance in Japanese men. Subjects and methods We used data from 4224 Japanese men, aged 43.3 ± 13.9 years, in this cross-sectional study. Balance, such as one leg with eyes closed balance was measured. In addition, cigarette smoking habits were obtained by well-trained medical staff. The effect of cigarette smoking on one leg with eye closed balance was evaluated. Results A total of 1613 men (38.2 %) had smoking habit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although it did not reach the established significance level, we have observed that the postural balance seems to be reduced in smokers. Interestingly, the association between smoking and poor postural balance has been already reported 27 . A large cohort study assessed the postural balance of smokers aged 20 years and the assessment was repeated at 53 years 28 .…”
Section: Discussionmentioning
confidence: 84%
“…Although it did not reach the established significance level, we have observed that the postural balance seems to be reduced in smokers. Interestingly, the association between smoking and poor postural balance has been already reported 27 . A large cohort study assessed the postural balance of smokers aged 20 years and the assessment was repeated at 53 years 28 .…”
Section: Discussionmentioning
confidence: 84%